Studi Komparatif Pemikiran Paulo Freire dan Ki Hajar Dewantara dalam Konteks Pendidikan Kritis - Fadhli, Rama (Yayasan Albahriah Jamiah Indonesia, 2025)
Education as an instrument of social transformation has been the focus of attention of many thinkers, including Paulo Freire and Ki Hajar Dewantara who have had a major influence in the development of critical education. The background of this study departs from the urgency of building an education system that is able to free students from structural and cultural domination that shackles their human potential. This study aims to comparatively examine the thoughts of Paulo Freire and Ki Hajar Dewantara in the context of critical education, by highlighting the similarities and differences between the two in terms of educational goals, the roles of teachers and students, and the pedagogical approaches used. The research method used is a qualitative study with a library approach, reviewing the primary and secondary works of both figures as well as a critical analysis of contemporary critical education theory. The results show that Paulo Freire emphasizes education as a praxis of liberation through horizontal dialogue, critical awareness (conscientization), and the destruction of the banking-style education model. Meanwhile, Ki Hajar Dewantara emphasizes the importance of contextual education and rooted in the nation’s cultural values, with the principle of “ing ngarso sung tulodo, ing madyo mangun karso, tut wuri handayani” as an educational leadership strategy. Both reject authoritarian approaches and position students as active subjects in the learning process. The conclusion of this study suggests that integrating Freire’s and Dewantara’s ideas can enrich critical education discourse in Indonesia, particularly in developing a dialogical, contextual, and transformative curriculum model.